2014
DOI: 10.1186/s13023-014-0162-0
|View full text |Cite
|
Sign up to set email alerts
|

Management of endocrino-metabolic dysfunctions after allogeneic hematopoietic stem cell transplantation

Abstract: Allogeneic hematopoietic stem cell transplantation is mainly indicated in bone marrow dysfunction related to blood diseases, but also in some rare diseases (adrenoleucodystrophy, mitochondrial neurogastrointestinal encephalomyopathy or MNGIE…). After decades, this treatment has proven to be efficient at the cost of numerous early and delayed side effects such as infection, graft-versus-host disease, cardiovascular complications and secondary malignancies. These complications are mainly related to the condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 60 publications
0
22
0
4
Order By: Relevance
“…Gonadal failure in adult patients post-HSCT was found at a frequency of 40.2% but according to other studies, it can reach 92% in males and 99% in females on long-term follow-up [8] when transplanted children were included. As previously described by others authors [5,[7][8][9][10][11][12][13][14][15][16], in our study risk factors for the development of hypogonadism were age at the transplant, type of conditioning and the treatments for the underlying disease (chemotherapy and ERT). A revision by Brennan, et al [6] showed that gonadal failure was associated with age at transplant, conditioning and underlying disease therapy.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Gonadal failure in adult patients post-HSCT was found at a frequency of 40.2% but according to other studies, it can reach 92% in males and 99% in females on long-term follow-up [8] when transplanted children were included. As previously described by others authors [5,[7][8][9][10][11][12][13][14][15][16], in our study risk factors for the development of hypogonadism were age at the transplant, type of conditioning and the treatments for the underlying disease (chemotherapy and ERT). A revision by Brennan, et al [6] showed that gonadal failure was associated with age at transplant, conditioning and underlying disease therapy.…”
Section: Discussionmentioning
confidence: 51%
“…The use of glucocorticoids for a long-term in a high dose can temporarily change the hypothalamus-pituitary-adrenal axis, as confirmed by Majhail, et al [20] and Vantyghem, et al [9], and could impair the assessment of adrenal function. Some of our patients were using glucocorticoids at the first visit to endocrine service, but during the follow-up we can distinguish them.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Для будущих исследований перспективным явля-ется более пристальное внимание к проблеме рацио-нального применения сахароснижающих препаратов для кардио-и вазопротекции у пациентов после алло-ТГСК с метаболическими расстройствами [19]. заключение Эндокринные дисфункции, дислипидемия и мета-болические расстройства являются актуальной пробле-мой у реципиентов после алло-ТГСК.…”
Section: Discussionunclassified